Isolation of human haematopoietic progenitor cells using monoclonal antibodies. - Beverley, P; Linch, D; Delia, D (1980)
Studies of the differentiation of human haematopoietic cells have been greatly advanced by the use of in vitro cloning techniques to enumerate the myeloid and erythroid progenitor cells which form colonies in semi-solid medium. The granulocytic/monocytic colony-forming cells (CFU-GM) and erythroid burst-forming cells (BFU-E) are thought to be mononuclear cells, similar in size to medium size lymphocytes, but their ontogenetic relationship to other progenitor cells and the putative pluripotential stem cell remains obscure. This is partly because elucidation of parent-progeny relationships requires the isolation of precursor cells before they acquire mature phenotypic characters. Physical methods have failed to separate CFU-GM cleanly from other cells because of their heterogeneity, and immunologically specific markers for human progenitor cells have not been reported. We report here that a fraction containing all the granulocytic/monocytic and erythroid progenitor cells, as well as cells which may be lymphoid progenitors, can be isolated from bone marrow using a combination of monoclonal antibodies.